Forensic Autopsy of Multiple Stab Wound - Perwira, Satria; Prasilia Ramadhani; Edwin Tambunan; Ahmad Yudianto (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Stabbing is the predominant form of homicidal violence globally, resulting in both physical impairment and death. A stab wound is the result of a forceful push from a sharp or blunt pointed object, resulting in a wound that is deeper than it is length. Case presentation: We present a case of a man who was found dead after being stabbed with a sharp weapon by his partner in a public area, with an open wound on the left chest. A forensic expert identified the body at Dr. Soetomo General Hospital, Surabaya, Indonesia. On external examination, we found 23 open wounds on several anatomical regions. Vital injuries include an open wound on the right side of the neck and the back of both sides of the chest. In an internal examination, we found both lungs looked shrunken, and blood was found in the right and left chest cavities. The stab wound to the right back penetrated the right lower lung and right liver lobe. The stab wound to the left back penetrated the lower left lung. Conclusion: A complete autopsy is vital to determine the cause, mechanism, and manner of death and to reconstruct the events before death.